2013
DOI: 10.1302/2046-3758.27.2000164
|View full text |Cite
|
Sign up to set email alerts
|

Time to surgery in acute rotator cuff tear

Abstract: AimsWe performed a systematic review of the literature to determine whether earlier surgical repair of acute rotator cuff tear (ARCT) leads to superior post-operative clinical outcomes.MethodsThe MEDLINE, Embase, CINAHL, Web of Science, Cochrane Libraries, controlled-trials.com and clinicaltrials.gov databases were searched using the terms: ‘rotator cuff’, or ‘supraspinatus’, or ‘infraspinatus’, or ‘teres minor’, or ‘subscapularis’ AND ‘surgery’ or ‘repair’. This gave a total of 15 833 articles. After deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
2
29
0
10
Order By: Relevance
“…Therefore, it is necessary to determine whether a patient is suffering from an acute or chronic rotator cuff tear prior to surgical intervention. However, it is challenging to distinguish among acute tears, acute-on-chronic tears, and chronic tears with acute symptoms, both on clinical grounds and using imaging modalities such as radiography, dynamic sonography, MRI, and arthroscopy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to determine whether a patient is suffering from an acute or chronic rotator cuff tear prior to surgical intervention. However, it is challenging to distinguish among acute tears, acute-on-chronic tears, and chronic tears with acute symptoms, both on clinical grounds and using imaging modalities such as radiography, dynamic sonography, MRI, and arthroscopy [16].…”
Section: Discussionmentioning
confidence: 99%
“…The delay in repair was also associated with decreasing greater tuberosity bone density, which may contribute to poor healing [12]. A systematic review by Mukovozov et al showed a trend suggesting that surgeries performed within three months of an acute rotator cuff tear were linked to better post-operative range of motion and Constant scores [13]. The authors did conclude that their findings should be interpreted with caution due to the limitations and bias inherent in case series as 11 of the 15 studies were retrospective, and there was not randomized controlled trials available for analysis.…”
Section: Acute/severe Rotator Cuff Tearsmentioning
confidence: 99%
“…28 A recent systematic review found a minimal difference in favour of the early surgery group (<3 months) but due to limitations and bias within the studies the results should be viewed with caution. 31 The authors also did not include non-surgical outcomes within their study. It has previously been reported that duration of symptoms is not related to the degree of muscle weakness, limited range of motion, tear size, fatty atrophy or validated patient reported outcome measures.…”
Section: Non-surgical Management Of Rotator Cuff Tearsmentioning
confidence: 99%